ABOUT THE UNIONS OF THE STATE - Milen IVANOV (Challenges of the Knowledge Society, 2019)
The report examines the current problems related to the mechanisms of the country's accession to different types of alliances. Analyzing the processes and mechanisms for decision-making at the state level, are made the logical for the state administration decisions, related to the adequacy of the inclusion of a country to such groups. The report examines the adequacy of the Bulgarian practice against the international standards for strategic decision making in the state policy and makes important practical conclusions and gives specific recommendations for optimization of the strategic planning and forecasting processes.